2015
DOI: 10.1509/jmr.13.0296
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Empathy Facilitates Egocentric Predictions of Consumer Preferences

Abstract: Common wisdom suggests that managerial empathy (i.e., the mental process of taking a consumer perspective) helps executives separate their personal consumption preferences from those of consumers, thereby preventing egocentric preference predictions. The results of the present investigation, however, show exactly the opposite. First, the authors find that managerial empathy ironically accelerates self-reference in predictions of consumer preferences. Second, managers’ self-referential tendencies increase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 63 publications
1
25
0
2
Order By: Relevance
“…Specifically, we ask whether adopting a customer orientation during the screening stage of the NPD process brings about unexpected and undesirable cognitive biases. Our investigation contributes to the viewpoint in the literature that marketing decisions are influenced by the cognitions of individual managers (e.g., Hattula et al 2015). In particular, we contribute to the growing recognition that cognitive biases influence marketing decisions in a variety of nonnormative ways, such as escalating commitment to new products that are failing (Biyalogorsky, Boulding, and Staelin 2006) and being unrealistically optimistic regarding judgmental forecasts of sales (Kahneman and Lovallo 1993).…”
mentioning
confidence: 79%
“…Specifically, we ask whether adopting a customer orientation during the screening stage of the NPD process brings about unexpected and undesirable cognitive biases. Our investigation contributes to the viewpoint in the literature that marketing decisions are influenced by the cognitions of individual managers (e.g., Hattula et al 2015). In particular, we contribute to the growing recognition that cognitive biases influence marketing decisions in a variety of nonnormative ways, such as escalating commitment to new products that are failing (Biyalogorsky, Boulding, and Staelin 2006) and being unrealistically optimistic regarding judgmental forecasts of sales (Kahneman and Lovallo 1993).…”
mentioning
confidence: 79%
“…5 In other words, the ironic monitoring process is considered equivalent to a "prime" of decision makers' personal preferences in the existing literature on suppression attempts (Higgins 1996;Macrae et al 1994;Wegner 2009). Moreover, it is well-documented that priming personal preferences inflates the effects of personal preferences on preference predictions (i.e., the FCE increases; Hattula et al 2015;Higgins 1996;Krueger and Clement 1994). We therefore expect that for low levels of preference certainty, preference suppression attempts will trigger a Wegner-type ironic monitoring process, which in turn increases the FCE.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
“…Moreover, Hattula et al (2015) have shown that marketers are also susceptible to the FCE and that the size of the FCE depends on marketers' level of empathy with consumers. Specifically, their studies indicate that instructing (vs. not instructing) marketing managers to empathize with consumers increases their susceptibility to the FCE.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Managers are not always able to empathize with customers' thoughts and feelings. Current research reveals a negative effect; managerial empathy may even facilitate egocentric predictions of consumer preferences (Hattula et al 2015), meaning that managers who try to develop empathy for the customer's situation reinforce their own prejudices. Furthermore, faked market research using personas can be misused very easily and retroactively to validate design and justify design decisions.…”
Section: Necessity Of a Social Science Foundation In Market Research mentioning
confidence: 90%